The role of supplier satisfaction survey in building partnerships - Blaženka Knežević; Miroslav Mandić; Antonija Lipovac Tolić (Ekonomski Vjesnik, 2022)
Purpose: The main goal of this paper’s research was to determine the role and justification of surveying supplier satisfaction in building partnerships. Methodology: To collect primary data, qualitative research was used, which was conducted in several phases. The study tested nine key criteria modelled on the work of Vos et al. (2016). The sample of key suppliers was determined from a non-probability sample of experts from eight strategic suppliers who agreed to participate in the research. A qualitative approach was used due to the small sample and the desire to apply a different approach since the authors used a quantitative approach in most of the analysed papers. Results: Research has shown that the key criteria for supplier satisfaction are reliability, communication, and operative excellence of the customer they work with. Conclusion: Any long-term and successful business relationship implies the satisfaction of all parties in the relationship. The concept of supplier satisfaction research is a business practice of a modest number of companies. Despite this, the research participants confirmed that there are solid arguments and interest in introducing this type of research and its continuous implementation. The recommendation is the systematic introduction of supplier relationship management and, as part of that, the introduction of the practice of conducting supplier satisfaction surveys.